A critical examination of language and community - Miller, Paul Chamness; Rubrecht, Brian G.; Mikulec, Erin A.; McGivern, Cu-Hullan Tsuyoshi (Readings in language studies., 2022)
A Critical Examination of Language and Community is the sixth volume of the Readings in Language Studies series published by the International Society for Language Studies, Inc. Edited by Paul Chamness Miller, Brian G. Rubrecht, Erin A. Mikulec, and Cu-Hullan Tsuyoshi McGivern, volume six sustains the society's mission to organize and disseminate the work of its contributing members through peer-reviewed publications. The book presents international perspectives on language and community through a variety of themes. A resource for scholars and students, A Critical Examination of Language and Community represents the latest scholarship in new and emergent areas of inquiry. Readings in Language Studies, Volume 6: A Critical Examination of Language and Community features international contributions that represent state-of-the-field reviews, multi-disciplinary perspectives, theory-driven syntheses of current scholarship, reports of new empirical research, and criti- cal discussions of major topics centered on the intersection of language and community. Consistent with the mission of ISLS, the collection of 14 chapters in this volume seeks to 'bridge arbitrary disciplinary territories and provide a forum for both theoretical and empirical research, from existing and emergent research methodologies, for exploring the relationships among language, power, discourses, and social practices.'